The evolving research of customer adoption of digital payment: Learning from content and statistical analysis of the literature - Alaa Mahdi Sahi; Haliyana Khalid; Alhamzah F. Abbas; Saleh F. A. Khatib (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The global spread and use of the internet and mobile phones has contributed to the development of digital payments. Despite its growth potential, until now there is a lack of research providing a comprehensive synthesis and analysis of factors affecting the use, adoption, and acceptance of digital payment methods. This study aims to address this gap by providing a comprehensive review of the related literature retrieved from Scopus and Web of Science databases. Following a systematic method, a final sample of 193 research articles was identified and analysed. The results highlight that a single theory has failed to comprehensively explain the complex nature of electronic payment adoption. The key limitation of the existing theories is their inability to consider the role of social and cultural facets in the adoption of new technology. While literature reviews are a widespread practice in business studies, there are scant reviews that use the systematic review methodology that aggregates knowledge using clearly defined processes and criteria. This is the first systematic review on electronic payment adoption, which structures the existing knowledge and provides directions for future research.
Keywords: 650; actual use; continuous use; ePayment; recommend; satisfaction; switch intention